Estudio de evaluación de obras existentes y prospección de futuras obras para el Instituto del Verbo Encarnado. - Alvarado Romero, Vanessa Thalía (2014)
The problems that are encountered in the soil where there is infrastructure (and the possibility of enlargement) require to deepen the analysis of geotechnical processes to optimize in this way the designs and provide mitigation measures to counteract the effects of the nature. The present project is a study of the problems existing in the sector El Carmen at the facilities of the Institute of the Incarnate Word, where an assessment has been carried out on the existing infrastructure and proposes the necessary mitigation measures. There was realized a set of activities aimed at obtaining the geotechnical parameters among which are the load-bearing capacity of the soil, collection of geological information, in addition to a topographic survey; with the information obtained and processed presents the designs of the works and mitigation measures. The proposed mitigation measurements are the construction of drainage works, construction of a retaining wall to gravity and a proposal of foundation with isolated plinths for the expansion of works. The project also includes the design of the slab for court and parking.